Características de consumo de antiagregantes plaquetarios orales en el servicio de cardiología y cirugía de tórax del hospital nacional edgardo rebagliati martins – essalud durante los meses enero-julio del año 2008” - Ghiglino Gonzales, Viviana (2009)
The present descriptive, transverse and retrospective study had as an objective to determine the characteristics of consumption of Antiplatelet oral therapy in the National Hospital Edgardo Rebagliati Martins during the months January-July of 2008. The population in study was shaped by all the hospitalized patients computerized records that consumed Acetil Salicilic Acid or Clopidogrel in the Service of Cardiology and Cardiovascular surgery of the Hospital Edgardo Rebagliati Martins during the months January-July of 2008, where was investigated: Consumption of Acetil Salicilic Acid and Clopidogrel expressed in daily definite dose (DDD) for 100 beds-days and consumer expenditure. The consumption of Acetil Salicilic Acid and Clopidogrel in the National Hospital Edgardo Rebagliati Martins during January-July of 2008 was 39.38 and 17.14 respectively that generate and expense of S/.171.9 for Acetil Salicilic Acid and S/.702 for Clopidogrel